1992
DOI: 10.1002/1097-0142(19920915)70:6<1625::aid-cncr2820700631>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Disseminated neuroblastoma (stage IV and IV-S) in the first year of life. Outcome related to age and stage

Abstract: Background. Infants (age 0–11 months) with disseminated neuroblastoma are known to have a better prognosis than older children with the disease, but there is little information regarding factors that influence the outcome of the disease in these patients. Methods. The authors report a series of 110 infants with disseminated neuroblastoma with disease diagnosed between March 1976 and February 1991 in 21 institutions participating in the Italian Cooperative Group on Neuroblastoma (ICGNB). Of the 110 infants, 34 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
52
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(55 citation statements)
references
References 18 publications
3
52
0
Order By: Relevance
“…The spread of tumor cells to bone marrow (BM) is a grim prognostic indicator for patients with neuroblastoma (NB), with the exception of infants (1). The search for BM infiltration is therefore of utmost importance for both staging and therapeutic purposes.…”
Section: Introductionmentioning
confidence: 83%
“…The spread of tumor cells to bone marrow (BM) is a grim prognostic indicator for patients with neuroblastoma (NB), with the exception of infants (1). The search for BM infiltration is therefore of utmost importance for both staging and therapeutic purposes.…”
Section: Introductionmentioning
confidence: 83%
“…This study confirms that stage 4s NB is associated with an excellent survival rate. Indeed, the OS is 88% and comparable to previous studies (Suarez et al, 1991;De Bernardi et al, 1992;Strother et al, 1995;Van Noesel et al, 1997;Katzenstein et al, 1998;Nickerson et al, 2000). We confirm that over onethird of patients have clinically favourable tumours without organ dysfunction despite widespread disease, and that for these patients careful observation is sufficient with a survival rate of 100%.…”
Section: Discussionmentioning
confidence: 99%
“…These observations suggest that in patients with rapidly expanding intra-abdominal disease, earlier and more intensive treatment may be necessary. As already reported, very young infants had a worse prognosis (De Bernardi et al, 1992;Katzenstein et al, 1998;Nickerson et al, 2000). In previous studies, infants less than 2 months at diagnosis were found to fare worse, although in some other studies the threshold was 1 or 3 months old.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately half of the children diagnosed with neuroblastoma have metastatic disease on diagnosis and, except for infants (De Bernardi et al, 1992), have a low probability of cure . The remaining children present with localised disease and have an overall better prognosis, mainly depending on the degree of tumour resection (Cecchetto et al, 1983;von Schweinitz et al, 2000).…”
mentioning
confidence: 99%